Where theories of terrain might land: Towards 'pluriversal' engagements with terrain. Issue 2 (July 2021) - Squire, Rachael
This brief commentary draws on Stuart Elden's thought provoking article, 'Terrain, Politics, History', to make two interventions. The first argues that understandings of terrain and Earth's materiality would be enriched by engaging with 'pluriversal' perspectives where Earth is inherently animated, lively, and heterogenous. This includes indigenous perspectives and those attending to non-human animal life. The second calls for a more concerted engagement within geography with terrains as voluminous constructs, whether that be in mountains, the air, or increasingly in artificial environments. It concludes by advocating for a further stretching of 'terrain' as presented in the paper to see where diverse understandings of terrain might land or indeed, climb, float, sink, or soar.